Pariah figures in Georg Simmel: the woman, the poor, the foreigner - da Silva Santos, Patrícia (2020)
This article presents some of ways that Georg Simmel’s sociology deals with the asymmetries found in relationships of social reciprocity, with reference to the figures of the poor individual, the woman and the stranger. The general argument is that each of these three categories relate to an omnipresent opposition in Simmel’s discussions, namely: the conflict between the individual and the group. In this sense, in their particular experiences, the woman, the poor individual and the stranger reflect problems associated with the rigidity of social forms. At the same time, the very asymmetry that is constitutive of their relationship with the groups can, in some cases, be used to renew social relations stiffened by the objective forms of modern society.